Evaluation of Operational Properties of Composite Reinforcement Used in Concrete Structures; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Rodevich V. V. (Diagnostics and Engineering of Novel Materials, 2014)
Title screen